Chabrolene, a Novel Norditerpene from the Bornean soft coral Nephthea sp. - Takahiro Ishii,; Takashi Kamada,; Phan, Chin-Soon; Charles S. Vairappan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Soft corals are often the research interest organism due to their structural diverse secondary metabolites with wide spectrum of biological activities range from antibacterial to anticancer potentials. The Borneo Island is rich in diversity of marine organisms including soft coral. Therefore, a population of Bornean soft coral belongs to genus Nephthea was collected from Mantanani Island (Sabah, Malaysia) which led to the isolation of a novel norditerpene, chabrolene (1) together with three known compounds (2-4). The chemical structure of 1 was determined by NMR and HREIMS data. Compound 1 exhibited repellent activity against the maize weevil Sitophilus zeamais.